Design of Local Exhaust Ventilation for Spray Booths: Proposed Study - Said, M. R; Hasan, Nor Halim; Leman, A.M. (ARPN, 2012)
Workers are exposed to contaminant at workplace. Employers in Malaysia shall comply with Factories and Machineries Act 1967 and Occupational Safety and Health 1994 to minimize the exposure that hazardous to workers health. Engineering control such as to provide Local Exhaust Ventilation (LEV) is to control contaminant to the employees. This report is a research proposal to carry out for Local Exhaust Ventilation study at Automobile Assembly Plant in Malaysia focusing in spray paint to look on current design and purpose new design and advanced material to the system. Data collections are based on survey questionnaires, chemical monitoring, LEV inspection, testing and examination. Expected results are comparison from experimental, analytical and finite-element used in automotive industries prediction of advanced material will propose to the systems.